Low-gas-production layered oxide positive electrode material, preparation method thereof and battery

By constructing a doped coated structure on the surface of the nickel-ferromanganese base layered oxide positive electrode material, the cyclic stability and rate performance challenges of the material are solved, the structural stability and electrochemical performance are improved, and the gas production is reduced.

CN119153641APending Publication Date: 2024-12-17LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411062168.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Ni-ferromanganese-based layered oxide positive electrode materials have challenges in cyclic stability and rate performance, and the improvement methods of the prior art such as surface coating, ion doping and nanocomposite structures have certain defects, making it difficult to achieve electrical properties and structures. Stable balance improvement.

Method used

By constructing a suitable doped coating structure on the surface of the copper-containing nickel iron-manganese base layered oxide positive electrode material, a specific coating material NaσNiaFebMncCudAeO2·Yx@MyOz, Yx enters the substrate in the form of surface doping, and MyOz is constructed in the form of coating. Surface cladding optimizes the structural stability and electrical properties of the material.

Benefits of technology

It significantly reduces the microcrack propagation and gas production problems during long-term operation of the material, improves the structural stability and electrochemical performance of the material, and ensures excellent performance in high-temperature cycle capacity retention and volume change rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004978242570000111
    Figure BDA0004978242570000111
  • Figure BDA0004978242570000121
    Figure BDA0004978242570000121
  • Figure HDA0004978242580000011
    Figure HDA0004978242580000011
Patent Text Reader

Abstract

The general formula of the low-gas-production layered oxide positive electrode material is Na sigma NiaFebMncCudAeO2. Yx at MyOz, 0.95 < sigma < = 1.05, 0 < a < = 0.4, 0 < b < = 0.4, 0 < c < = 0.5, 0 < d < = 0.1, 0 < = e < = 0.01, a + b + c + d + e = 1, z = 3x / 2 + ny / 2, n is the ion valence state of M, and 0.5 < = x / y < = 2; m is one or more of Al, Zr and B, and A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd and Ce; and the mass ratio N of Yx (at) MyOz to NiaFebMncCudAeO2 is more than 0% and less than or equal to 1%. The structural stability and the electrical property of the material are effectively improved, and the gas production problem of the material is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium electric materials, in particular to a layered oxide positive electrode material capable of reducing high-temperature gas generation, a preparation method thereof and a battery. Background Art

[0002] As an emerging energy storage technology, sodium-ion batteries show great application prospects in the field of energy storage due to their abundant raw materials, low cost and environmental friendliness. In particular, layered oxide materials are favored for their high theoretical capacity and good electrochemical properties. However, nickel-iron-manganese-based layered oxide positive electrode materials still face challenges in cycle stability and rate performance in practical applications. Although copper doping can improve the electrochemical properties of the material, it may also cause lattice distortion and stress accumulation, thereby promoting the formation of microcracks and side reactions in the electrolyte, affecting the performance and safety of the battery.

[0003] During the charge and discharge process, the surface of the positive electrode material is prone to side reactions with the electrolyte due to its unevenness and large surface area, resulting in oxidation of the surface structure and the generation of microcracks. As the number of battery cycles increases, the continuous erosion of the electrolyte may cause corrosion and expansion of grain boundary cracks, further destroying the structural integrity of the positive electrode material and affecting the electrochemical performance of the battery. In addition, the increase in particle refinement makes this degradation trend more significant.

[0004] In the synthesis of layered oxides, the direct use of copper-containing NiFeMn precursors or the addition of copper sources and sodium salts during the sintering process may lead to the degradation of electrochemical performance and air stability, accompanied by gas generation problems.

[0005] In order to improve these problems, some methods are used in the prior art, such as:

[0006] Surface coating: By coating a protective layer on the surface of the positive electrode material, such as Al2O3, TiO2, etc., direct contact with the electrolyte is reduced and side reactions are reduced.

[0007] Ion doping: By doping other elements such as Zr, Ta, etc. into the material, the lattice stability is enhanced and the formation of microcracks is reduced.

[0008] Nanocomposite structure: Construct a nanocomposite structure and utilize the properties of different materials to synergistically improve the overall performance of the material.

[0009] Morphology control: By controlling the morphology of the material, such as spherical, fibrous, etc., stress concentration can be reduced and the formation of microcracks can be reduced.

[0010] However, these methods also have some defects: surface coatings often weaken ion conductivity while blocking contact with the electrolyte; ion doping may affect the initial electrochemical properties of the material and lead to decreased cycle or rate performance due to unstable doping; the construction of nanocomposite structures increases structural complexity, and the compatibility of the framework structure needs to be improved; morphology control may require additional templates or additives, increasing the risk of material inhomogeneity.

[0011] In summary, although the existing technology provides some means to improve microcracks and gas generation problems, further optimization is still needed to achieve a balanced improvement in electrical performance and structural stability. Summary of the invention

[0012] In view of the above-mentioned problems in the prior art, the present invention provides a low-gas-generating layered oxide positive electrode material, a preparation method thereof, and a battery. By adopting a specific coating material to construct a suitable doping coating structure on the surface of a copper-nickel-iron-manganese-based layered oxide positive electrode material, the structural stability and electrical properties of the material are effectively improved, and the microcrack expansion and gas generation problems of the material under long-term operation are greatly reduced.

[0013] The low-gassing layered oxide positive electrode material proposed in the present invention has the following general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z , where 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e In the surface structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mnc Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0014] The low-gassing layered oxide positive electrode material of the present invention can achieve at least one of the following performance indicators:

[0015] i. Particle size distribution D50 satisfies 3μm≤D50≤12μm;

[0016] ii. The assembled button cell has a 50-week 1C cycle capacity retention rate of ≥97% at 2.5-4.05V;

[0017] iii. The assembled button cell has a discharge capacity of ≥125mAh / g in the first week at 2.5-4.05V;

[0018] iv. The assembled soft-pack battery has a capacity retention rate of ≥97% and a volume change rate of ≤10% at 2.5-4.0V, high temperature of 45°C, and 300 cycles of 1C.

[0019] Further, in the general formula of the above-mentioned material of the present invention,

[0020] As some preferred solutions, 0.2≤a≤0.4, 0.2≤b≤0.4, 0.2≤c≤0.5;

[0021] As some further preferred embodiments, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35;

[0022] As some further preferred embodiments, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10;

[0023] As some further preferred schemes, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10; 1≤x / y≤2.

[0024] The low-gassing layered oxide positive electrode material proposed in the present invention is prepared by the following method:

[0025] S1: Prepare a layered oxide sintered intermediate product, the layered oxide sintered intermediate product has the following general formula: Na σ Ni a Fe b Mn c Cu d A eO2, wherein 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, and A is one or more elements selected from Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, and Ce;

[0026] S2: The layered oxide sintered intermediate is mixed with the Y source additive and the M source additive according to a stoichiometric ratio, and then sintered at least once at 550° C. to 850° C.

[0027] In some embodiments, the layered oxide sintering intermediate of step S1 is prepared by the following method: mixing one of the following ingredients according to a stoichiometric ratio: (1) nickel-iron-manganese precursor, copper source, sodium source, other doping source (source A); or (2) nickel-iron-manganese-copper precursor, sodium source, other doping source (source A); and then sintering at 700°C to 1200°C in air or oxygen atmosphere.

[0028] In some further schemes, the optimization of the sintering system of step S1 is conducive to obtaining an intermediate with uniform structure. Under the optimized system, the sintering temperature is 900°C to 1100°C, the sintering time is 10-23h, and the heating rate is 1-10°C / h.

[0029] In some further embodiments, the D50 of the nickel-iron-manganese precursor and / or the nickel-iron-manganese-copper precursor in step S1 is 2-7 μm, and the D50 of the copper source, the sodium source and / or other doping sources is 1-3 μm.

[0030] In some further embodiments, the nickel iron manganese precursor has the following general formula: Ni a Fe b Mn c (OH)2, nickel iron manganese copper precursor has the following general formula: Ni a Fe b Mn c Cu d (OH)2, wherein a, b, c, and d conform to the theoretical stoichiometric ratio of the general formula of layered oxide positive electrode materials.

[0031] In some further embodiments, the sodium source in step S1 includes one or more of sodium carbonate, sodium hydroxide, sodium nitrate, sodium sulfate, sodium chloride, metallic sodium, sodium metal alloy, etc., preferably sodium carbonate.

[0032] In some further embodiments, the copper source in step S1 includes one or more of copper oxide, copper sulfate, copper nitrate, copper chloride, metallic copper, copper metal alloy, copper acetate, organic copper salt, etc., preferably copper oxide.

[0033] In some further embodiments, the other doping sources (A source) in step S1 include one or more of corresponding oxides, carbonates, nitrates, sulfates, chlorides, etc., preferably oxides.

[0034] In some embodiments, the sintering temperature of step S2 is 650° C. to 800° C., the sintering time is 5-20 hours, and the heating rate is 1-10° C. / h.

[0035] In some embodiments, the D50 of the Y source additive and / or the M source additive in step S2 is 0.2-5 μm.

[0036] In some embodiments, the Y source additive and / or the M source additive in step S2 include one or more of the corresponding oxides and hydroxides.

[0037] On the other hand, the present invention also provides a positive electrode or a battery made of the above-mentioned low-gas-generating layered oxide positive electrode material.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] The present invention adds Y in the form of coating on the surface of the copper-nickel-iron-manganese-based layered oxide positive electrode material. x M y O z To construct a stable doped coating layer, Y enters the surface of the substrate in the form of surface doping to form a surface doping layer, and has the function of diffusion doping into the substrate, M y O z An ultra-thin oxygen-rich bonding coating is formed on the surface of the material. The Y-Cu strengthening phase brought by doping and the original YO strong bond play a "pinning" effect, optimizing the material's structural strength and corrosion resistance. y O z The oxygen-rich bonded coating layer isolates the positive electrode material from the electrolyte due to the acid and alkali resistance of the coating material itself, reducing the occurrence of side reactions; and by adjusting the material ratio to precisely control the co-doping coating, the material structural strength and surface interface stability are improved, reducing and avoiding side reactions; EPMA, particle size, charge retention performance and gas production characterization prove that within the control range, the additive has a significant improvement on the electrochemical performance, material air stability, and electrochemical cycle stability, while the gas production is significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 This is the EPMA-Al image analysis result of the layered oxide positive electrode material of Example 1 of the present invention.

[0042] Figure 2 This is the EPMA-Y image analysis result of the layered oxide positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0044] The low-gassing layered oxide positive electrode material proposed in the present invention has the following general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z , where 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e In the surface and internal structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0045] The present invention adds Y in the form of coating on the surface of the copper-nickel-iron-manganese-based layered oxide positive electrode material. x M y O z To construct a stable doped coating layer, Y x M y O z Yttrium (Y) and Al / Zr / B oxides are introduced into the coating layer. As one of the rare earth elements, Y has a larger atomic radius. Compared with Al / Zr / B, Y has a relatively lower bonding ability with O. It is easy to enter the matrix (Ni) by filling the surface defects in the case of co-coating. a Fe b Mn c Cu d A e O2) surface and inhibit crack growth. At the same time, when Y enters the matrix surface and diffuses inward, it can form a Y-Cu strengthening phase with the doped Cu in the matrix, thereby improving the strength and corrosion resistance of the doped surface. Al / Zr / B has a strong bonding ability with O. After combining with Y, it can form an ultra-thin oxygen-rich bonding coating layer on the material surface. The surface coating layer M constructed by Al / Zr / B and O y O z It has good chemical stability and mechanical strength, which further improves the material surface's ability to resist electrolyte corrosion and improve microcrack expansion; in addition, Y x M y O z It can also serve as a nucleation substrate, which helps to build M y O z The grain refinement during the coating process is conducive to the establishment of an ultra-thin and uniform coating layer, greatly reducing the amount of coating material added. x M y O z The co-coating effect greatly improves the problems of surface microcracks and electrolyte side reactions of copper-nickel-iron-manganese-based layered oxide positive electrode materials, and improves the gas production results of the materials.

[0046] The low-gassing layered oxide positive electrode material of the present invention can achieve at least one of the following performance indicators:

[0047] i. Particle size distribution D50 satisfies 3μm≤D50≤12μm;

[0048] ii. The assembled button cell has a 50-week 1C cycle capacity retention rate of ≥97% at 2.5-4.05V;

[0049] iii. The assembled button cell has a discharge capacity of ≥125mAh / g in the first week at 2.5-4.05V;

[0050] iv. The assembled soft-pack battery has a capacity retention rate of ≥97% and a volume change rate of ≤10% at 2.5-4.0V, high temperature of 45°C, and 300 cycles of 1C.

[0051] In some embodiments, the material of the present invention has the general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z , where 0.95<σ≤1.05, 0.2≤a≤0.4, 0.2≤b≤0.4, 0.2≤c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e In the surface and internal structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0052] In some embodiments, the material of the present invention has the general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z, where 0.95<σ≤1.05, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e In the surface and internal structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0053] The optimized ratio of nickel, iron and manganese atoms is beneficial to improving the framework stability of the layered structure and is beneficial to Y x @M y O z During the construction of the surface coating layer, Y migrates and diffuses toward the substrate.

[0054] In some embodiments, the material of the present invention has the general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z , where 0.95<σ≤1.05, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Nia Fe b Mn c Cu d A e In the surface and internal structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0055] Optimizing and controlling the doping amount of copper and other elements in the material matrix is ​​also beneficial to optimizing and improving the strengthening effect of Y-Cu.

[0056] In some embodiments, the material of the present invention has the general formula: Na σ Ni a Fe b Mn c Cu d A e O2·Y x @M y O z , where 0.95<σ≤1.05, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 1≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e In the surface and internal structure of O2, M y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e The mass ratio N of O2 is 0%<N≤1%.

[0057] Additive Y x M y O z The optimized balance of Y and M in the doped coating material increases the reasonable proportion of Y in the doped coating material, promotes the doping diffusion of Y, and promotes the role of Y in promoting M y O z Efficiency in grain refinement.

[0058] The low-gassing layered oxide positive electrode material proposed in the present invention is prepared by the following method:

[0059] S1: Prepare a layered oxide sintered intermediate product, the layered oxide sintered intermediate product has the following general formula: Na σ Ni a Fe b Mn c Cu d A e O2, wherein 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, and A is one or more elements selected from Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, and Ce;

[0060] S2: The layered oxide sintered intermediate is mixed with the Y source additive and the M source additive according to a stoichiometric ratio, and then sintered at least once at 550° C. to 850° C.

[0061] In the above method, the preparation of the layered oxide sintering intermediate product in step S1 ensures the stability of the layered oxide positive electrode material matrix and provides a structural basis for stable doping and coating; step S2 is sintered at a relatively low temperature to promote the coating layer M y O z The formation of Y element and the effective diffusion doping of Y element to the surface and inside of the substrate. The preparation method of the layered oxide sintering intermediate is not specifically limited, and there is a relatively mature preparation process in the prior art.

[0062] In some embodiments, the layered oxide sintering intermediate of step S1 is prepared by the following method: mixing one of the following ingredients according to a stoichiometric ratio: (1) nickel-iron-manganese precursor, copper source, sodium source, other doping source (source A); or (2) nickel-iron-manganese-copper precursor, sodium source, other doping source (source A); and then sintering at 700°C to 1200°C in air or oxygen atmosphere.

[0063] In some further schemes, the optimization of the sintering system of step S1 is conducive to obtaining an intermediate with uniform structure. Under the optimized system, the sintering temperature is 900°C to 1100°C, the sintering time is 10-23h, and the heating rate is 1-10°C / h.

[0064] In some further schemes, the particle size control of step S1 is conducive to obtaining a layered oxide positive electrode material with controllable particle size, and together with the coating layer raw material, a good doping coating structure is formed. The specific optimized particle size control is that the D50 of the nickel iron manganese precursor and / or the nickel iron manganese copper precursor is 2-7 μm, and the D50 of the copper source, sodium source and / or other doping sources is 1-3 μm. Under the raw material particle size control, the sintered product obtained in step S1 can be crushed to obtain a layered oxide sintered intermediate with a D50 of 3-12 μm. Provide good coating preparation for the coating layer.

[0065] In some further embodiments, the nickel iron manganese precursor has the following general formula: Ni a Fe b Mn c (OH)2, nickel iron manganese copper precursor has the following general formula: Ni a Fe b Mn c Cu d (OH)2, wherein a, b, c, and d conform to the theoretical stoichiometric ratio of the general formula of layered oxide positive electrode materials. The precursor material can be obtained by purchase or mature preparation process means.

[0066] In some further embodiments, the sodium source in step S1 includes one or more of sodium carbonate, sodium hydroxide, sodium nitrate, sodium sulfate, sodium chloride, metallic sodium, sodium metal alloy, etc., preferably sodium carbonate.

[0067] In some further embodiments, the copper source in step S1 includes one or more of copper oxide, copper sulfate, copper nitrate, copper chloride, metallic copper, copper metal alloy, copper acetate, organic copper salt, etc., preferably copper oxide.

[0068] In some further embodiments, the source A in step S1 includes one or more of corresponding oxides, carbonates, nitrates, sulfates, chlorides, etc., preferably oxides.

[0069] In some schemes, the optimization of the sintering system of step S2 is conducive to obtaining a uniform coating layer. Under the optimized system, the sintering temperature is 650℃~800℃, the sintering time is 5-20h, and the heating rate is 1-10℃ / h. The coating sintering is carried out at a temperature not higher than that of the layered oxide sintered intermediate product. At the same time, a properly high temperature within the range is selected to promote the doping diffusion of Y and the formation of an ultra-thin coating layer M under the condition of stabilizing the layered oxide sintered intermediate product matrix. y O zformation.

[0070] In some embodiments, the D50 of the Y source additive and / or the M source additive in step S2 is 0.2-5 μm, which is well coordinated with the layered oxide sintered intermediate product in step S1 in terms of particle size control.

[0071] In some embodiments, the Y source additive and / or the M source additive in step S2 include one or more of the corresponding oxides and hydroxides.

[0072] The following provides specific implementation cases to further fully illustrate the present invention.

[0073] Example 1

[0074] Weigh the precursor Ni with D50≈4.5μm 0.34 Fe 0.33 Mn 0.33 (OH)2, copper oxide with D50≈2μm, weigh sodium carbonate (impurity element A≈0, negligible) when sodium ratio δ=1.00, mix the above raw materials according to the designed stoichiometric ratio, sinter at 960℃ in air atmosphere for 24h at a heating rate of 2.5℃ / min, crush the fired intermediate material, add Y2O3 and Al2O3 at a mass ratio of 0.5% relative to the intermediate material, the molar ratio of Y2O3 and Al2O3 is 1:1, at this time x / y=1, mix evenly, sinter for the second time at 650℃ for 18h at a heating rate of 2.5℃ / min, and obtain sample A01 after crushing, the chemical formula is

[0075] NeNi 0.3298 Fe 0.3201 Mn 0.3201 Cu 0.03 O2·Y@AlO3.

[0076] Example 2

[0077] The same method as in Example 1 is used, except that the precursor Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 was replaced by directly using the precursor Ni with D50≈4.5μm 0.33 Fe 0.32 Mn 0.32 Cu 0.03 (OH)2, no copper oxide is added, and the other steps remain unchanged.

[0078] Example 3

[0079] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are replaced by Y2O3 and ZrO2 in a molar ratio of 1:1, and x / y=2 at this time, and the other steps remain unchanged.

[0080] Example 4

[0081] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are replaced by Y2O3 and B2O3 in a molar ratio of 1:1, and x / y=1 at this time, and the other steps remain unchanged.

[0082] Example 5

[0083] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are replaced with a molar ratio of 1:2, and x / y=0.5 at this time, and the other steps remain unchanged.

[0084] Example 6

[0085] The same method as in Example 1 is adopted, except that the secondary sintering temperature is changed to 800° C., and the other steps remain unchanged.

[0086] Example 7

[0087] The same method as in Example 1 is used, except that the precursor Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 is replaced by the precursor Ni 0.4 Fe 0.2 Mn 0.4 (OH)2, the other steps remain unchanged.

[0088] Example 8

[0089] The same method as in Example 1 is used, except that the precursor Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 is replaced by the precursor Ni with D50≈6μm 0.34 Fe 0.33 Mn 0.33 (OH)2, the other steps remain unchanged.

[0090] Example 9

[0091] The same method as in Example 1 is used, except that the feed ratio of copper oxide is increased, the doping amount of Cu is increased, and the NaNi product is obtained. 0.3098 Fe 0.3001 Mn 0.3001 Cu 0.09 O2·Y@AlO3.

[0092] Example 10

[0093] The same method as in Example 1 is adopted, except that the copper oxide with D50≈2 μm is replaced by copper oxide with D50≈1 μm, and the other steps remain unchanged.

[0094] Embodiment 11

[0095] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are added at a mass ratio of 1% relative to the intermediate material, and the other steps remain unchanged.

[0096] Comparative Example 1

[0097] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are not added for coating.

[0098] Comparative Example 2

[0099] The same method as in Example 1 is adopted, except that Y2O3 and Al2O3 are added at a mass ratio of 2% relative to the intermediate material, and the other steps remain unchanged.

[0100] Comparative Example 3

[0101] The same method as in Example 1 is used, except that the precursor Ni 0.34 Fe 0.33 Mn 0.33 (OH)2 is replaced by the precursor Ni with D50≈9μm 0.34 Fe 0.33 Mn 0.33 (OH)2, the other steps remain unchanged.

[0102] Comparative Example 4

[0103] The same method as in Example 1 is adopted, except that the secondary sintering temperature is changed to 950° C., and the other steps remain unchanged.

[0104] Comparative Example 5

[0105] The same method as in Example 1 is adopted, except that the molar ratio of Y2O3 to Al2O3 is replaced with 1:4, that is, x / y=0.25, and the other steps remain unchanged.

[0106] The above examples and comparative examples were tested by the following methods.

[0107] Battery assembly: The positive electrode materials prepared in each embodiment and each comparative example were used as active materials, mixed according to the mass ratio of active material: SP: PVDF of 90:5:5, and NMP was added to make a viscous glue, which was coated on aluminum foil and baked in a vacuum drying oven at 120°C for 12 hours to obtain a positive electrode sheet. A 2032 button cell was assembled in an Ar protective glove box using a metal sodium sheet as the counter electrode, glass fiber (Waterman) as the diaphragm, and 1 mol / LNaPF6 EC / DMC=1:1 (Alfa) as the electrolyte.

[0108] Electrochemical performance test: The battery was tested in the voltage range of 2.5-4.0V, cycled at 0.1C for 3 weeks and 1C for 50 weeks, and the average discharge capacity of each battery at 0.1C for 3 weeks and its corresponding first efficiency (first coulomb efficiency), and the discharge capacity of the first week and 50 weeks of 1C cycle were recorded respectively.

[0109] Element analysis test: The layered oxide positive electrode materials in the embodiments and comparative examples were selected, sectioned using an argon ion polisher, and subjected to EPMA image analysis to check the element distribution inside and on the surface of the materials.

[0110] Gas production volume test: Assemble the soft-pack battery, use the water displacement method, immerse the soft-pack battery in water, and measure and record the volume change before and after the drainage cycle as the gas production of the soft-pack battery.

[0111] The above test results are listed in Table 1 and Figure 1-2 middle.

[0112] Table 1

[0113]

[0114]

[0115] By comparing Examples 1-11 and Comparative Examples 1-2, it can be found that the present invention uses additive Y x M y O z The surface of the Cu-Ni-Fe-Mn-based layered oxide positive electrode material is doped and coated, and Y is diffused into the surface and inside of the matrix and M y O z Construct the surface coating to form Y x @M y O z , which improves the corrosion resistance and stability of the substrate surface and reduces gas production. At the same time, an ultra-thin coating layer is constructed through grain refinement, and the electrochemical performance is also significantly improved.

[0116] Examples 1-2 show that similar effects can be achieved by introducing Cu into the matrix in different ways. Figure 1-2EPMA also found that Y entered the matrix surface and diffused into the interior, while Al gathered on the surface of the material, proving that Y x @M y O z The effect of doping and coating co-modification. 0.34 Fe 0.33 Mn 0.33 The mixed sintering of (OH)2 and copper oxide has a better effect. The possible reason is that the present invention improves the dispersion effect of Cu in the matrix by optimizing the suitable sintering system.

[0117] Examples 1, 3, and 4 show that Y and Zr and B have similar effects in forming a surface doping modified coating layer, and the electrochemical performance and gas production are basically equivalent or even slightly superior. The possible reason is that Zr and B have a greater bonding advantage than Al in bonding with oxygen to construct an oxygen-rich surface coating layer.

[0118] Examples 1, 3, 4, and 5 also embody the additive Y x M y O z The influence of different doping amounts of elements in the M is shown in Figure 2. When 1≤x / y≤2 (Examples 1, 3, and 4), compared with when x / y=0.5 (Example 5), although there is little difference in gas production, there is a slight advantage in both first efficiency and capacity retention. This is due to the doping diffusion of Y and the role of Y in promoting M y O z The efficiency of grain refinement is related to that of the ratio x / y (Comparative Example 5). Too small x / y (Comparative Example 5) results in insufficient doping diffusion of Y in the matrix and has limited effect on promoting grain refinement, resulting in poor results.

[0119] Examples 1, 6 and Comparative Example 4 demonstrate the effect of secondary sintering temperature. Secondary sintering is beneficial to promoting the doping diffusion of Y and the coating layer M. y O z Too low a sintering temperature is not conducive to the doping diffusion, while too high a sintering temperature may cause the destruction of the matrix structure or excessive side reactions of the coating layer.

[0120] Examples 1 and 7 show that the matrix framework ratio also has an impact on the stability of doping coating. The optimized nickel-iron-manganese element ratio is conducive to providing a more stable structure and promoting Y doping stability.

[0121] Examples 1, 8, 10 and Comparative Example 3 explored the effect of raw material particle size and confirmed that optimized particle size control is conducive to the formation of a good doping coating structure. Excessively large precursor particles (Comparative Example 3) are not conducive to the formation of a uniform coating layer, and have adverse effects on rate, circulation and gas production.

[0122] Examples 1 and 9 illustrate that the introduction of an appropriate amount of Cu into the matrix is ​​beneficial to the effective improvement of the overall performance.

[0123] Examples 1, 11 and Comparative Example 2 discuss the effect of the amount of coating layer used, and demonstrate the performance advantages of the present invention when the amount of ultra-thin coating layer used is used.

[0124] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A low-gassing layered oxide cathode material having the following general formula: Na σ Ni a Feb b Mr c Cu d A e O 2 ·Y x @M y O z , in, 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, z=3x / 2+ny / 2, n is the ion valence of M, 0.5≤x / y≤2; M is one or more of Al, Zr, B, A is one or more of Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; element Y enters Na in the form of surface doping σ Ni a Fe b Mn c Cu d A e O 2 In the surface structure of y O z Construct the surface coating layer in the form of coating, Y x @M y O z with Ni a Fe b Mn c Cu d A e O 2 The mass ratio N is 0%<N≤1%.

2. The low-gassing layered oxide positive electrode material according to claim 1, It is characterized in that The low-gassing layered oxide positive electrode material of the present invention can achieve at least one of the following performance indicators: i. Particle size distribution D50 satisfies 3μm≤D50≤12μm; ii. The assembled button cell has a 50-week 1C cycle capacity retention rate of ≥97% at 2.5-4.05V; iii. The assembled button cell has a discharge capacity of ≥125mAh / g in the first week at 2.5-4.05V; iv. The assembled soft-pack battery has a capacity retention rate of ≥97% and a volume change rate of ≤10% at 2.5-4.0V, high temperature of 45°C, and 300 cycles of 1C.

3. The low-gassing layered oxide positive electrode material according to claim 1, It is characterized in that In the general formula of the material of the present invention, Na σ Ni a Fe b Mn c Cu d A e O 2 ·Y x @M y O z middle, As some preferred solutions, 0.2≤a≤0.4, 0.2≤b≤0.4, 0.2≤c≤0.5; As some further preferred embodiments, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35; As some further preferred embodiments, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10; As some further preferred schemes, 0.3≤a≤0.35, 0.3≤b≤0.35, 0.3≤c≤0.35, 0.03<d≤0.09, d / e≥10; 1≤x / y≤2.

4. A method for preparing a low-gassing layered oxide positive electrode material according to any one of claims 1 to 3, comprising the following steps: S1: Prepare a layered oxide sintered intermediate product, the layered oxide sintered intermediate product has the following general formula: Na σ Ni a Fe b Mn c Cu d A e O 2 , in, 0.95<σ≤1.05, 0<a≤0.4, 0<b≤0.4, 0<c≤0.5, 0<d≤0.1, 0≤e≤0.01, a+b+c+d+e=1, A is one or more elements selected from Co, Li, K, Al, Mg, Ti, Zn, Ca, Sb, Sc, Zr, Nb, V, Ga, Sr, Ba, Nd, Ce; S2: The layered oxide sintered intermediate is mixed with the Y source additive and the M source additive according to a stoichiometric ratio, and then sintered at least once at 550° C. to 850° C.

5. The preparation method according to claim 4, It is characterized in that Step S1: The layered oxide sintered intermediate is prepared by the following method: mixing one of the following ingredients according to a stoichiometric ratio: (1) nickel-iron-manganese precursor, copper source, sodium source, other doping source (source A); or (2) nickel-iron-manganese-copper precursor, sodium source, other doping source (source A); and then sintering at 700°C to 1200°C in air or oxygen atmosphere.

6. The preparation method according to claim 5, It is characterized in that The optimization of the sintering system in step S1 is conducive to obtaining an intermediate with uniform structure. Under the optimized system, the sintering temperature is 900°C to 1100°C, the sintering time is 10-23h, and the heating rate is 1-10°C / h; Preferably, the D50 of the nickel-iron-manganese precursor and / or the nickel-iron-manganese-copper precursor in step S1 is 2 to 7 μm, and the D50 of the copper source, the sodium source and / or other doping sources is 1 to 3 μm; Preferably, the nickel-iron-manganese precursor has the following general formula: Ni a Fe b Mn c (OH) 2 , the nickel-iron-manganese-copper precursor has the following general formula: Ni a Fe b Mn c Cu d (OH) 2 , where a, b, c, and d conform to the theoretical stoichiometric ratio of the general formula of layered oxide cathode materials; Preferably, the sodium source in step S1 includes one or more of sodium carbonate, sodium hydroxide, sodium nitrate, sodium sulfate, sodium chloride, metallic sodium, sodium metal alloy, etc., preferably sodium carbonate; Preferably, the copper source in step S1 includes one or more of copper oxide, copper sulfate, copper nitrate, copper chloride, metallic copper, copper metal alloy, copper acetate, organic copper salt, etc., preferably copper oxide; Preferably, the other doping sources in step S1 include one or more of corresponding oxides, carbonates, nitrates, sulfates, chlorides, etc., with oxides being preferred.

7. The preparation method according to claim 4, It is characterized in that The sintering temperature of step S2 is 650°C to 800°C, the sintering time is 5-20h, and the heating rate is 1-10°C / h; Preferably, the D50 of the Y source additive and / or the M source additive in step S2 is 0.2 to 5 μm; Preferably, the Y source additive and / or the M source additive in step S2 include one or more of the corresponding oxides and hydroxides.

8. A positive electrode or a battery, comprising the low-gassing layered oxide positive electrode material according to any one of claims 1 to 3, or the low-gassing layered oxide positive electrode material obtained by the preparation method according to any one of claims 4 to 7.